Assessment of financial management practices in the poultry industry using the Neutrosophic VIKOR method - Mayorga Díaz Mónica; Kevin Steven Yánez Pazuña; Jessica Paola Yánez Pazuña; Jorge Fernando Goyes García (Journal of Fuzzy Extension and Applications)
The study analyzed the impact of the COVID-19 pandemic on small poultry businesses in Cotopaxi, Ecuador, noting a decline in revenue and a need for immediate financial strategies. The objective was to identify operational and financial management practices, along with criteria for assessing the financial health of these organizations. The research used reliable secondary sources from 2018-2020 and employed the neutrosophic VIKOR method to prioritize management practices based on utility, regret, and effectiveness indexes, considering sustainability and operational efficiency. Findings indicated that cost control, performance measurement, and risk management are key practices for optimizing profitability and sustainability in the poultry sector. The study concluded that the strategic adoption of these practices enhances competitiveness and promotes sustainable development. Comparative studies and environmental sustainability analyses were recommended to strengthen the sector further globally.